Une caractérisation des indicateurs élaborés dans l’activité. Perspectives sémiotiques sur la formation professionnelle - Christian Dépret; Lucile Vadcard (Recherches en Éducation)
Our subject of interest is the notion of indicator in the domain of analyzing the activity with a training point of view. While escaping the dualist trap, this concept allows conceiving an individual who doesn’t lay eyes on an objective reality, but observes concrete elements which are potentially significant (potential indicators or signs). This semiotic rendition is not exclusive, and must be articulated with the theoretical approaches of the field of vocational didactics (we particularly underline the articulation with constructivism). We present three categories of indicators and the inherent question of their validity. Finally, we develop a “method of indicators” through their characterization in five dimensions: relativity, subjectivity, safety, responsibility and convertibility. Each of these dimensions connects the modalities of the interpretative process to aspects of the activity that they are likely to influence (for example, if the safety of the index chain should always be suspected, in reality, it is done only for specific values of the index). We highlight these connections by examples in the field of maieutic (for example, midwifery students are reassured by the technical nature of a long index chain while experienced midwives seek to verify by a direct access the safety of an imagery or tracing).